Arsitektur Lawang Sewu sebagai Landmark dan Destinasi Wisata Kota Semarang, Jawa Tengah - Esya Fairuz Nurfadillah; Jason Derian Richardo (Lembaga Pengembangan Kinerja Dosen, 2023)
Lawang Sewu is a historic building owned by PT KAI in Operational Area 4 Semarang, Central Java. Lawang Sewu is a relic from the Dutch Colonial period. Now Lawang Sewu has become a cultural heritage building that is included in the building protection law. In this museum we can find the legacy of the old PT KAI. Lawang Sewu is also one of the leading tourist attractions in the city of Semarang and witnessed the 5-day battle in Semarang which took place from 14 to 19 August 1949 and is marked by the location of the Tugu Muda Monument which is on the west side of Lawang Sewu or more precisely at the Jalan Pandanaran roundabout. As an architectural and tourist object, Lawang Sewu has the value needed in the definition of a monument and monumental nature. These values include aspects of history, technology, architecture, and culture. Currently the Lawang Sewu building houses a collection of trains in Indonesia from time to time. Collections such as Alkmaar, Edmonson machines, calculating machines, typewriters, replica steam locomotives, securities, and several other collections. This place is also often used for community activities such as exhibitions, festivals, art performances, shooting, wedding parties and photo shoots.